2022
DOI: 10.1002/jcsm.13051
|View full text |Cite
|
Sign up to set email alerts
|

Measured weight loss as a precursor to cancer diagnosis: retrospective cohort analysis of 43 302 primary care patients

Abstract: Background Unexpected weight loss is a presenting feature of cancer in primary care. Data from primary care are lacking to quantify how much weight loss over what period should trigger further investigation for cancer. This research aimed to quantify cancer diagnosis rates associated with measured weight change in people attending primary care. Methods Retrospective cohort study of primary care electronic health records data linked to the Surveillance, Epidemiology, and End Results cancer registry (Integrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Sojourn time for CRC in the preclinical state has consistently been estimated to be about 3–6 years [ 10 12 ]. This prediagnostic period often goes along with weight loss [ 7 , 55 , 56 ]. Since most of the case–control studies ascertained BMI close to the time of diagnosis, such studies, and systematic reviews and meta-analyses that included them, are likely to have underestimated the relationship between overweight and obesity and CRC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sojourn time for CRC in the preclinical state has consistently been estimated to be about 3–6 years [ 10 12 ]. This prediagnostic period often goes along with weight loss [ 7 , 55 , 56 ]. Since most of the case–control studies ascertained BMI close to the time of diagnosis, such studies, and systematic reviews and meta-analyses that included them, are likely to have underestimated the relationship between overweight and obesity and CRC.…”
Section: Discussionmentioning
confidence: 99%
“…However, a large 2017 meta-analysis reported even stronger associations with colorectal adenomas, the precursors of most CRCs, with a risk increase by more than 40% for both overweight and obesity [ 6 ]. Furthermore, there is evidence that CRC patients may experience substantial weight loss in the preclinical phase prior to diagnosis [ 7 ], suggesting that the strength of the association of overweight and obesity with CRC risk may have been underestimated in epidemiological studies due to prediagnostic weight loss. In case–control studies, BMI is often reported for the time close to or shortly before diagnosis among cases.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 displays the comparison of FFP, WGS, NRS2002, and GLIM, which reflect the commonality and individuality of the tools. Weight loss was the only criterion shared by the four tools, which is not only for nutrition assessment but also a sensitive precursor for tumor diagnosis, especially for pancreatic cancer ( 23 ). Besides weight loss, NRS2002 and GLIM contain age, BMI, intake reduction, and assessment of disease (inflammation burden), which are relatively more comprehensive to assess the nutrition status.…”
Section: Discussionmentioning
confidence: 99%
“…For example, risk factors such as cigarette smoking or adverse weight profiles may co-occur, are known to independently and jointly influence risk for many cancers (17)(18)(19)(20)(21), and have quantitatively important causal influences on health economic outcomes (22)(23)(24)(25). Cohort studies (for example (26)) that attribute costs to cancer patients may account for direct costs following a diagnosis of cancer, but cannot reflect all causal impacts associated with liability to cancer or cancer diagnoses because in general it is not possible to identify all confounding variables, to assess their contribution without measurement error, to condition away their influence in quantitative analysis, or to include all downstream causal impacts.…”
Section: Introductionmentioning
confidence: 99%